The changing face of cardiovascular disease 2000–2012: An analysis of the world health organisation global health estimates data - McAloon, Christopher J; Boylan, Luke M; Hamborg, Thomas; Stallard, Nigel; Osman, Faizel; Lim, Phang B; Hayat, Sajad A (International journal of cardiology, 2016)
The pattern and global burden of disease has evolved considerably over the last two decades, from primarily communicable, maternal, and perinatal causes to non-communicable disease (NCD). Cardiovascular disease (CVD) has become the single most important and largest cause of NCD deaths worldwide at over 50%. The World Health Organisation (WHO) estimates that 17.6 million people died of CVD worldwide in 2012. Proportionally, this accounts for an estimated 31.43% of global mortality, with ischaemic heart disease (IHD) accounting for approximately 7.4 million deaths, 13.2% of the total. IHD was also the greatest single cause of death in 2000, accounting for an estimated 6.0 million deaths. The global burden of CVD falls, principally, on the low and middle-income (LMI) countries, accounting for over 80% of CVD deaths. Individual populations face differing challenges and each population has unique health burdens, however, CVD remains one of the greatest health challenges both nationally and worldwide. [Display omitted] •Variation in cardiovascular disease burden follows an epidemiological transition.•Cardiovascular disease burden follows risk factor profiles within ethnic constructs.•Cardiovascular disease is set to remain a leading global health burden.